Mono-6-Substituted Cyclodextrins—Synthesis and Applications - Petr Kasal; Jindřich Jindřich (Molecules, 2021)
Cyclodextrins are well known supramolecular hosts used in a wide range of applications. Monosubstitution of native cyclodextrins in the position C-6 of a glucose unit represents the simplest method how to achieve covalent binding of a well-defined host unit into the more complicated systems. These derivatives are relatively easy to prepare; that is why the number of publications describing their preparations exceeds 1400, and the reported synthetic methods are often very similar. Nevertheless, it might be very demanding to decide which of the published methods is the best one for the intended purpose. In the review, we aim to present only the most useful and well-described methods for preparing different types of mono-6-substituted derivatives. We also discuss the common problems encountered during their syntheses and suggest their optimal solutions.